PENGEMBANGAN MEDIA PERMAINAN PUZZLE KARTU BERGAMBAR UNTUK MELATIH KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN - Janiar, Despy; Marmawi, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to develop picture card puzzle game media to train early reading skills in children aged 5-6 years to determine the attractiveness and feasibility of use, and children after using picture card puzzle game media to train early reading skills in children. The method used by researchers is the development of Research and Development (RD), namely the development of picture card puzzle game media. This game media development model was developed based on the development model (Analysis, Design, Development, Implementation, Evaluation). The data collection tools used were: first a material expert questionnaire and second a media expert questionnaire. The test subjects in this research were children in Gudang Hulu Village, Selimbau District. The results of the research developed obtained a design in the form of a picture card puzzle game media to train early reading skills in children aged 5-6 years. The percentage of eligibility is 96% by material experts, 87% by media experts. based on the results of the percentage that the media developed by the researcher was declared suitable for use as a learning medium.